DEIKSIS PERSONA, RUANG, DAN WAKTU DALAM NOVEL HELLO KARYA TERE LIYE - Husnawati; Sudika, Nyoman; Setiawan, Irma (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to identify and analyze the forms, functions, and meanings of person, spatial, and temporal deixis in the novel Hello by Tere Liye using a pragmatic approach. The study focuses on three types of deixis: person deixis, spatial deixis, and temporal deixis. Data collection was carried out using the listening and note-taking method, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the novel contains three main types of deixis: person deixis, spatial deixis, and temporal deixis, with person deixis being the most dominant type. Each type of deixis has functions and meanings that depend on its context of use. This study offers novelty as no previous research has specifically examined the use of deixis in the novel Hello by Tere Liye.